Pengembangan Sistem Informasi Praktik Kerja Lapangan Berbasis Website SMK Negeri 1 Pengasih - Bagus Santosa; Nurkhamid (Department of Electronics and Informatics Engineering Education, 2024)
This research aims to: (1) Developing a web-based student internship information system that solves data management, information delivery, and internship service at SMK N 1 Pengasih; (2) Executing comprehensive quality assessments on the developed system, aligning with ISO 25010 standards, focusing on the characteristics of usability, functional suitability, performance efficiency, reliability, and maintainability. Employing a Research and Development (R&D) approach within the Waterfall Model's five stages (communication, planning, modeling, construction, and deployment), this research was conducted at SMK N 1 Pengasih. The results of this research indicate that: (1) The web-based student internship information system is developed and aptly serves data management, information delivery, and internship service at SMK N 1 Pengasih; (2) The web-based student internship information system meets ISO 25010 software quality standards as follow: Usability characteristic is categorized as “Very Suitable” with a percentage of 85.92%, functional suitability characteristic is categorized as “Very Suitable” with a percentage of 100%, reliability characteristic meets the standard with a percentage of 99.73%, performance efficiency characteristic is categorized as “Good” with performance score of 97.32%, structure score of 94.36%, and a load time of 1.27 seconds, and maintainability characteristic is categorized as “Highly Maintainable” with a MI value of 90.50.